Survey of agriculture in Latin America and the Caribbean 1990-2000 (ECLAC SantiagoCL, 2001)
Analyzes the production and foreign trade of agricultural goods in the region during the 1990s. Evaluates the principal trends and the overall performance of the sector.
Keywords: AGRICULTURE